THE RELATIONSHIP OF FORMAL EDUCATION WITH MEN'S ATTITUDES TOWARDS SEXUAL BEHAVIOR IN INDONESIA 2017 - Seri Aryati; Ratri Purnama Dewi (Department of Geography Education, Faculty of Social Sciences, Universitas Negeri Medan, 2020)
The phenomenon of dating in adolescents is considered common nowadays. The data shows that 84% of male adolescents in Indonesia claim to have been dating, 4% higher than female adolescents in 2017. Dating has a big risk, which leads to premarital sexual behavior. The attitude of men towards premarital sexual behavior in Indonesia varies widely, from agreeing to disagreeing. This study aims to describe the relationship between the level of formal education and attitudes of male adolescents towards premarital sexual behavior in Indonesia in 2017. Kendall's Tau correlation test was used to determine whether there was a relationship between the two variables tested, namely the level of education and attitudes towards premarital sexual behavior. The data used is secondary data from the 2017 Indonesian Demographic and Health Survey (IDHS). The sample in this study amounted to 12.987 scattered throughout Indonesia. Quantitative descriptive analysis and spatial analysis were used to describe the distribution of correlation results in each province. Through this research, it can be seen that nationally there is a significant and positive relationship between the level of formal education and the attitudes of male adolescents towards premarital sexual behavior in Indonesia in 2017. However, when viewed from the distribution in each province, the correlation results vary.